Aqueous extract of Lithospermi radix attenuates oxaliplatin-induced neurotoxicity in both in vitro and in vivo models. Issue 1 (December 2016) - Cho, Eun-Sang; Yi, Jin-Mu; Park, Jong-Shik; Lee, You; Lim, Chae; Bang, Ok-Sun; Kim, No
Abstract Background Oxaliplatin can induce peripheral neuropathy (OXIPN) as an adverse side effect in cancer patients. Until now, no effective preventive or therapeutic drug has been developed; therefore, the dose-limiting factor of OXIPN is still an obstacle in the use of oxaliplatin to treat cancer patients. In the present study, we report for the first time that the aqueous extract ofLithospermi radix (WLR) can attenuate the OXIPN in both in vitro and in vivo neuropathic models. Methods The protective effect of WLR on OXIPN was evaluated in vitro by quantifying nerve growth factor (NGF)-stimulated neurite outgrowth in PC12 cells treated with a combination of oxaliplatin and WLR. The neuroprotective potential of WLR was further confirmed by measuring the changes in nociceptive sensitivities to external mechanical stimuli in neuropathic animals induced by oxaliplatin. Histological and immunohistochemical studies were further done to examine the effect of WLR in mouse spinal cords and footpads. Results Oxaliplatin-induced neurotoxicity in NGF-stimulated PC12 cells. It could reduce the lengths and branching numbers of neuritis in NGF-stimulated PC12 cells. Co-treatment of WLR rescued the differentiated PC12 cells from the neurotoxicity of oxaliplatin. In a chronic OXIPN animal model, administration of oxaliplatin i.p. induced enhanced nociceptive sensitivity to mechanical stimuli (25.0 to 72.5 % of response rate) along with spinal activation of microglias and astrocytes and loss of intraepidermal nerve fibers in footpads, which is remarkably suppressed by oral administration of WLR (67.5 to 35 % of response rate at the end of experiment). Cytotoxicity of oxaliplatin determined in human cancer cells was not affected irrespective of the presence of WLR. Conclusions In conclusion, we demonstrated that WLR can attenuate OXIPN in both in vitro and in vivo experimental models, which may be in part attributed to its anti-inflammatory activity in the spinal cord and its neuroprotective potential in the peripheral nerve system without affecting the anti-tumor potential of oxaliplatin. Therefore, WLR could be considered as a good starting material to develop a novel therapeutic agent targeting OXIPN. However, further studies should be done to elucidate the underlying mechanism such as molecular targets and active constituent(s) in WLR with neuroprotective potential.